A New Hybrid Algorithm and Its Numerical Realization for a Quasi-Nonexpansive Mapping (Communications in Mathematical Research, 2019)
The purpose of this article is to propose a new hybrid projection methodfor a quasi-nonexpansive mapping. The strong convergence of the algorithm is provedin real Hilbert spaces. A numerical experiment is also included to explain the effectivenessof the proposed methods. The results of this paper are interesting extensionsof those known results.